Evaluación de la extracción de los fitonutrientes de la cáscara de cebolla de bulbo (Allium cepa L.) (2023)
The objective of this degree project is to evaluate the extraction of flavonoids from the Allium cepa onion peel, comparing conventional and unconventional extraction techniques, in order to select an extraction method that presents adequate conditions to obtain a higher yield. of flavonoids and carry out their respective conceptual design. In order to carry out the general objective, bibliographic information was collected on the phytochemical properties of the Allium cepa onion, its varieties, as well as the structure of the polyphenols, mainly the flavonoid quercetin, and its industrial application. It was also necessary to collect data on physicochemical characteristics, in order to establish the selection parameters of raw material for extraction. Conventional and unconventional extraction techniques were evaluated using the decision matrix based on Pugh's methodology.